Medication Adherence Through Structured mHealth Education In Pulmonary TB: A Literature Review - Adenan, Antelina (Poltekkes Kemenkes Banjarmasin, 2024)
Introduction: Pulmonary tuberculosis (TB) is a global health concern. The lengthy treatment process, which lasts at least 6 months, can lead to non-adherence due to boredom, resulting in reluctance to continue treatment. In foreign countries, non-adherence is addressed through interventions such as the use of mobile phones or mHealth, and several studies have highlighted the benefits of mHealth for TB patients. Objective: This study aims to describe the benefits of mHealth on the adherence of TB patients, including treatment evaluation, self-efficacy, and medication adherence. Methods: A literature review was conducted to analyze selected studies and generate new ideas. Discussion: By reviewing and analyzing 10 selected journals, it was concluded that mHealth applications and video Directly Observed Treatment, Short-course (vDOTS) are highly effective in improving medication adherence among pulmonary TB patients. Recommendations: Further research is encouraged to develop mHealth applications that enhance medication adherence among TB patients and to test their effectiveness